ANALISIS STRATEGI KOMUNIKASI DAN KREATIVITAS KONTEN KREATOR DALAM MEMPROMOSIKAN PRODUK SHOPEE AFFILIATE MELALUI MEDIA SOSIAL - Praulina, Farina Farina; Marlena, Novi (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This research aims to analyze the communication strategies and creativity of content creators in promoting products on social media, with a focus on the Shopee Affiliate program. Identify strategies and creative elements used by content creators to increase the effectiveness of product promotions on social media. This research uses observation and interview methods with four informants who are active as content creators on various social media platforms. Data was collected through observation, interviews and documentation. The research results show that content creators develop promotional media through the use of attractive visuals, educational content, language that is easy to understand, and the use of viral elements such as hashtags and popular sounds. These strategies help create interesting content and can increase engagement with the audience. The use of effective communication strategies and creativity in creating content has been proven to increase the success of Shopee Affiliate product promotions on social media. Content creators need to continue to innovate and follow trends to maintain the appeal of the content they create.